2018
DOI: 10.1186/s12881-018-0536-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing reveals a stop-gain mutation of PKD2 in an autosomal dominant polycystic kidney disease family complicated with aortic dissection

Abstract: BackgroundAutosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disorder characterized by progressive cyst formation and expansion in the kidneys, which culminates in end-stage renal disease. Aortic dissection is a rare vascular complication of ADPKD and related literature is currently limited.Case presentationIn this report, we described a patient with asymptomatic Stanford B aortic dissection. Further investigation revealed a positive family history of ADPKD and normal rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Approximately 10% of patients with ADPKD have no detectable PKD1 or PKD2 mutation, which may be attributed to the current lack of effective testing methods or to similar kidney cysts caused by other gene mutations (5,6). ADPKD is characterized by numerous enlarged cysts in the bilateral kidneys and liver, in addition to specific rare manifestations in other organs, including the pancreas, cerebral vasculature, aortic arch and seminal vesicles (7)(8)(9)(10). In the case of the present study, a novel frameshift PKD1 mutation was identified in ADPKD, which additionally caused epididymal cysts and azoospermia.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of patients with ADPKD have no detectable PKD1 or PKD2 mutation, which may be attributed to the current lack of effective testing methods or to similar kidney cysts caused by other gene mutations (5,6). ADPKD is characterized by numerous enlarged cysts in the bilateral kidneys and liver, in addition to specific rare manifestations in other organs, including the pancreas, cerebral vasculature, aortic arch and seminal vesicles (7)(8)(9)(10). In the case of the present study, a novel frameshift PKD1 mutation was identified in ADPKD, which additionally caused epididymal cysts and azoospermia.…”
Section: Introductionmentioning
confidence: 99%